2017
DOI: 10.1002/ange.201704804
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Oxidative (4+3) Cycloadditions between Allenamides and Furans through Bifunctional Hydrogen‐Bonding/Ion‐Pairing Interactions

Abstract: BINOL-based N-trifluoromethanesulfonyl phosphoramides catalyzet he enantioselective (4+ +3) cycloaddition between furans and oxyallyl cations,the latter being generated in situ by oxidation of allenamides.T he chiral organic phosphoramide counteranion is proposed to engage in the activation of the oxyallyl cation intermediate through cooperative hydrogen-bonding and ion-pairing interactions,enabling an efficient chirality transfer that providethe final adducts with high diastereo-and enantioselectivities.R ema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…In 2008, the same group described the Tetrakis[(R)-(+)-N-(pdodecylphenylsulfonyl)prolinato]dirhodium(II) (Rh 2 (R-DOSP) 4 )-catalyzed reaction of vinyl diazoacetate 35 and furan 36 for the generation of formal [4 + 3] cycloadducts 37 with excellent stereoselectivities (up to >94% de and 98% ee). This reaction was smoothly proceeded by a tandem cyclopropanation/Cope rearrangement followed by stereoselective tautomerization (Figure 11) [25]. In 2017, Jacobsen and coworkers reported that H-bond donors such as chiral squaramide 42 could activate relatively unreactive electrophiles for promoting enantioselective reactions in the following manner.…”
Section: Enantioselective [4 + 3] Cyclization (Or Annulation) Reactio...mentioning
confidence: 99%
“…In 2008, the same group described the Tetrakis[(R)-(+)-N-(pdodecylphenylsulfonyl)prolinato]dirhodium(II) (Rh 2 (R-DOSP) 4 )-catalyzed reaction of vinyl diazoacetate 35 and furan 36 for the generation of formal [4 + 3] cycloadducts 37 with excellent stereoselectivities (up to >94% de and 98% ee). This reaction was smoothly proceeded by a tandem cyclopropanation/Cope rearrangement followed by stereoselective tautomerization (Figure 11) [25]. In 2017, Jacobsen and coworkers reported that H-bond donors such as chiral squaramide 42 could activate relatively unreactive electrophiles for promoting enantioselective reactions in the following manner.…”
Section: Enantioselective [4 + 3] Cyclization (Or Annulation) Reactio...mentioning
confidence: 99%